Effect of supplemental grain sorghum and overseeding with ladino clover on grazing and subsequent feedlot performance of steers early-intensively grazed on acremonium coenophialum - infected tall fescue pastures - Coffey, K.P.; Moyer, Joseph L.; Lomas, Lyle W.; Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty mixed breed steers (avg. wt. 560 lb.) were used to evaluate the effect on grazing gain and subsequent feedlot performance of different management options for steers early-intensively grazing Acremonium coenophialuminfected tall fescue pastures. Steers were allotted to pastures of infected fescue pastures or infected fescue overseeded with ladino clover and received no supplement or were offered grain sorghum at .25% of their body weight. Neither supplementation nor overseeding affected grazing or feedlot performance. However, grain supplementation on overseeded pastures reduced subsequent feedlot feed efficiency (P<.10). These management options did not substantially affect grazing or subsequent feedlot performance by steers early-intensively grazing infected fescue pastures.
Keywords: Beef; Tall fescue; Acremonium coenophialum; Ladino clover; Grain sorghum